?Quién soy yo? A fragmentação do sujeito mexicano em La frontera de cristal, de Carlos Fuentes - Silva, Luciano Prado da (2010)
This M.A. thesis proposes to discuss ways in which Carlos Fuentes s novel La frontera de cristal (1995) problematizes the historical repulsion/fascination between Mexicans and Anglos . Almost 200 years ago, the advance of the U.S. border collided with Mexico a fledgling nation in search of political identity and unity. Since then, the two countries established relations across both national and individual borders. In the construction of Fuentes s work, one of the foremost elements that demands attention is the representation of how notions of nationality become unsettled for men and women who experience the border as inbetweenness, as a Third Nation. Also worthy of note is the representation of Mexican vitality vis-à-vis State corruption, as well as the humiliation of being considered second-class U.S. citizens from el otro lado . Taking these points into consideration, the present study aims at offering an inquiring gaze into the complex history of cultural collisions and intersections which continue to mark Mexico-U.S. relations.